Laparoscopic Liver Resection : Theory and Techniques - Liu, Rong (Springer Netherlands : Imprint: Springer, 2017)
This book provides a comprehensive guide to the use of laparoscopic resection in the treatment of surgical liver lesions. As it introduces the steps and key techniques of laparoscopic anatomical liver resection, it will be of great interest to surgeons and physicians working in this area. Though each chapter covers a different technique, all chapters are written in a uniform style, including indications and contraindications, surgical steps, key techniques, complications and notes. This book provides readers with an overview of the current state of the art and deeper understanding of laparoscopic liver resections.
Keywords: Medicine.; Hepatology.; Minimally invasive surgery.; Surgical oncology.; elektronické knihy; electronic books